1977
DOI: 10.1073/pnas.74.3.1242
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative correlation of dopamine-dependent adenylate cyclase with responses to levodopa in various mice.

Abstract: We obtained 12 groups of mice with widely different neurological responses to levodopa by selecting them from different strains and submitting some of them to pretreatments. We scored the symptoms evoked by a standardized dose of levodopa in one subgroup from each group. We tested another subgroup for activation of an adenylate cyclase [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1] by a standardized dose of dopamine added to homogenates of the caudate nuclei of the brains of these mice. Both sets of tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For example, CBA mice have 25 to 50% fewer nigral DA neurons [57] and striatal D A receptors [62] than some other strains. Strain differences in DA-activated adenyl cyclase [63] indicate genetic influences on number or functions of striatal neurons. Such strain differences permit study of how genetic factors influence the effects of striatal lesions.…”
Section: Genotype and Manifestations Of Neurological Agingmentioning
confidence: 99%
“…For example, CBA mice have 25 to 50% fewer nigral DA neurons [57] and striatal D A receptors [62] than some other strains. Strain differences in DA-activated adenyl cyclase [63] indicate genetic influences on number or functions of striatal neurons. Such strain differences permit study of how genetic factors influence the effects of striatal lesions.…”
Section: Genotype and Manifestations Of Neurological Agingmentioning
confidence: 99%
“…the hypothalamic hormone that inhibits the release of melanocyte-stimulating hormone from the anterior pituitary gland.3-6 The extra-endocrine effects of 1 were first demonstrated by Plotnikoff et al7 with Everett's Dopa potentiationtest.8 In this test 1 was found to potentiate the behavioral effects of L-3,4-dihydroxyphenylalanine (L-Dopa) in both normal and hypophysectomized mice. Subsequent studies with 1 have also shown that this tripeptide antagonizes the central and peripheral effects of oxotremorine,9,10 reverses the sedative effects of deserpidine,11 potentiates the behavioral effects of apomorphine,12 attenuates puromycin-induced amnesia,13 and facilitates the development of morphine dependence.14 Moreover, a number of preliminary clinical studies have indicated that 1 may be of potential value in the treatment of Parkinson's disease 15,…”
mentioning
confidence: 99%